The effect of special exercises using water resistance in developing special strength and its effect on achievement - Hilal, Saeed Alwan; Chaleefah, Rafaa Rashid (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to use water resistance training to develop special strength in the aqueous medium for triple jump players and to identify the level of special strength for triple jump players in the aqueous medium, as well as to identify the level of performance and achievement development after using the aqueous medium. The research hypotheses included there are statistically significant differences in the level of the special strength tests between the pre and post tests after using the aqueous medium among the members of the research sample and in favor of the post test, and there are statistically significant differences in the level of performance and achievement between the tribal and the post exams among the members of the research sample and in favor of the post test. The researcher used the experimental approach to design the one group, that is, the pre and post test for one group, as the sample consisted of (5) players representing the national team for athletics in the triple jump, where the vocabulary of the training curriculum was started, the researcher addressed a number of theoretical studies in training with resistors and training conditions Resistors and how to design resistors programs, as well as dealing with resistance training in water, the benefits of using resistance training in water, the types of resistors in water, as well as the stages of technical performance in a triple jump, as well as physical characteristics of performance and the method of repetitive training The researcher used video imaging for the purpose of evaluating the technical performance of the triple jump, on which it was based in preparing the training curriculum using water resistance. After statistically processing the data, the researcher concluded that the proposed training curriculum was effective in the development of the force characterized by speed for the members of the research sample, which confirms that there is an evolution in the reactions of the working muscles in the lower limbs as a result of resistance training inside the water, which gave a positive return on the kinematic paths of the anatomical joints For these parts, as the results of the statistical treatments showed significant differences between the pre and post tests, and in favor of the post test for the members of the research sample. And the use of jumping exercises with rapid reflexes contributed to the excitement of these muscles, which contributed to the development of physical and motor efficiency within the movement requirements and the distinctive mechanical conditions for it. I also concluded that the continuation of training according to the approach prepared by the researcher in the aqueous medium has strengthened the increase of the efficiency of the muscular nervous system to adjust, adapt, and regulate the different motor processes that are commensurate with the technical performance of the triple jump, where the use of new exercises strengthens and contributes to the integration of different functions and is consistent with this difference and was This is evident through the technical level of performance. And it appeared that the members of the research sample who were exposed to different resistances inside the water have relatively integrated their control over the motor work during the performance of this effort and this means increasing the efficiency of the nervous system for them as a result of these exercises. And controlling the increase in the water level by increasing or decreasing has contributed to controlling the intensity of training and its graduation, and it has contributed to achieving control of the various rapid movements in the strength training that was taking place in the aqueous medium.